Synthesis and characterization of ricehusk activated carbon by torrefaction,Desilicationand alkalies based approach: STUDY OF RICE HUSK ACTIVATED CARBON BY TOLEA (Indian Journal of Engineering and Materials Sciences (IJEMS), 2023)
Challenges come from global warming and environmental pollution, which leads to the requirement of sustainable carbon-rich precursors for the synthesis of carbon materials. This study has been carried out to demonstrate the attempt of utilizing agricultural bio waste as Rice Husk (RH) as it is abundantly available, environmentally friendly, and low cost and a kind of renewable precursor material for the production of activated carbon. Activated rice husk-based porous carbon with honeycomb-shaped porosity was synthesized by torrefaction of finely powdered rice husk in a tubular furnace. Pyrolyzed rice husk carbon (RHC) was Desilicated by reflux method by mixing sodium carbonate solution with RHC to remove the silica layer so as to enhance the porosity of rice husk carbon. Desilicated RHC was mixed with mixed alkaline metal base hydroxides at a specific heating rate. The effect of saturating the carbon with mixed activating agents at different mass ratios was also studied. The confirmation of rice husk activated carbon (RHAC) has been confirmed by different techniques such as Scanning Electron Microscopy (SEM), X-ray diffraction analysis (XRD), Energy Dispersive X-Ray Analysis (EDX). The interlayer spacing (d002) of the RHAC1 and RHAC2 samples are 0.39 nm and 0.34 nm. These values are greater than the interlayer spacing for graphite (0.335 nm). This shows the distorted structure with low graphitization level for both samples. It was recognized that apparently amorphous-shaped RHAC was obtained along with meso-micro hierarchical porosity in topography. The ash yield of rice husk carbon obtained after Pyrolysis was found to be 43.8% which was obtained by weighing rice husk samples once it was cooled down in a few hours. The use of this activated rice husk carbon can be used in the fabrication of energy storage devices featuring the concepts of green energy.